2001
DOI: 10.1046/j.1365-2346.2001.00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of costs of total intravenous anaesthesia with propofol and remifentanil vs. balanced anaesthesia with isoflurane and fentanyl

Abstract: We conclude that propofol and remifentanil is more cost-effective than isoflurane/fentanyl due to its better recovery profile, reduced total direct costs and higher patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
1
20
0
4
Order By: Relevance
“…Patient satisfaction with the anesthetic was the same in both groups, which is in accordance with the literature [21].…”
Section: Process Times and Patient Satisfactionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patient satisfaction with the anesthetic was the same in both groups, which is in accordance with the literature [21].…”
Section: Process Times and Patient Satisfactionsupporting
confidence: 91%
“…The use of short-acting anesthetic drugs, such as remifentanil and propofol can possibly reduce the process times for general anesthesia [21]. In our study, we found differences in the "incision to closure" time as well as in the time to "induction complete".…”
Section: Process Times and Patient Satisfactionmentioning
confidence: 49%
“…in the last decade, the development of new protocols for balanced anaesthesia has been carried out in human [17,18,21,34,47,50], whereas the last two papers about balanced anaesthesia in swine were from 90 th years [16,56]. effectively, in veterinary practice inhalant anesthetic agents are the preferred method for maintenance of general anaesthesia since they are easy to be administered, the depth of anaesthesia can be rapidly and predictably modulated, and the recovery time is rapid [31].…”
Section: Discussionmentioning
confidence: 99%
“…B. die Aufwachraumzeit durch die Verwendung teurer, aber kurz wirksamer Substanzen deutlich verkürzt werden. Epple et al [12] konnten nachweisen, dass die Verwendung von Propofol und Remifentanil kosteneffektiver ist als eine Narkose mit Isofluran und Fentanyl, da die Aufwachzeit verkürzt wird und so die Gesamtkosten verringert werden.…”
Section: Diskussionunclassified